Ki67 is a biological marker of malignant risk of gastrointestinal stromal tumors: A systematic review and meta-analysis. Issue 34 (August 2017) - Zhou, Yu; Hu, Wenqing; Chen, Ping; Abe, Masanobu; Shi, Lei; Tan, Si-yuan; Li, Yong; Zong, Liang
Abstract: Background: Ki67 is a good marker of cell proliferation in a variety of tumors. High ki67 levels are usually associated with poor prognosis. However, the relationship between Ki67 expression and the risk of malignancy of gastrointestinal stromal tumors (GISTs) is still poorly defined. The current meta-analysis was initiated to address this issue. Methods: Studies reporting Ki67 expression and the risk of malignancy in GIST were found by searching Cochrane Library, PubMed, Medline, and Embase until October 31, 2016. A total of 9 studies involving 982 patients were included. Pooled odds ratio (OR) estimates and 95% confidence intervals (CIs) were calculated using a fixed-effect model. Results: Meta-analysis showed no significant difference in the incidence of Ki67 overexpression between the very low NIH group and the low NIH group (OR: 0.66, 95% CI: 0.25–1.76; P = .41, P heterogeneity = .25). However, the incidence of Ki67 overexpression gradually increased from the low NIH group to the high NIH group (OR: 0.46, 95% CI: 0.27–0.80; P = .005, P heterogeneity = .13) and (OR: 0.22, 95% CI: 0.15–0.34; P < .00001, P heterogeneity = .33). Conclusions: There were more GIST patients with Ki67 overexpression in the intermediate and high NIH groups than in the low NIH group. Ki67 overexpression may be a useful marker of the risk of malignant GIST transformation.